CHEMICAL DISSOLUTION OF NICKEL (II) OXIDE AND HYDROXIDE IN AMINO ACID SOLUTIONS - Ivanov, S.V. (Proceedings of National Aviation University (archive), 2005)
Simulation experimenting has been used to analyze thermodynamics of chemical dissolution of nickel (II) oxide and hydroxide in solutions containing various amino acids. Allowance for complexation, protonation and hydrolysis processes has been found to be a must for adequate description of chemical processes.